Lactobacillus (Limosilactobacillus) reuteri: a probiotic candidate to reduce neonatal diarrhea in calves - Schwaiger, Karin; Storch, Julia; Bauer, Christoph; Bauer, Johann (Frontiers in Microbiology, 2023)
Background Diarrhea in newborn calves is considered life-threatening and results in large economic losses in dairy farms. Recently, we showed that (i) Lactobacillus (Limosilactobacillus; L.) reuteri is the dominant Lactobacillus species in the feces of healthy calves during the first week of life, (ii) in calves with diarrhea on day 2 postpartum, lactobacilli were significantly reduced even up to 24 h before the onset of clinical signs, and (iii) when the concentration of L. reuteri in the feces increased, the probability of occurrence of diarrheal disease decreased. Objective These studies were designed to demonstrate whether oral administration of preselected L. reuteri isolates can reduce the incidence of diarrhea in newborn calves on dairy farms. Microorganisms 46 L. reuteri isolates from 2-day-old healthy calves were available from a previous study. Animals 170 newborn calves of Simmental breed of 10 dairy farms in Bavaria (Germany), were included in the study; of 166 animals the data could be evaluated. Methods Microbiological (antibiotic sensitivity test, acid and bile salt stability test, antimicrobial activity of the supernatants), molecular biological (PCR, RAPD-PCR) and toxicological methods (MTT test) were used to select and to characterize suitable L. reuteri isolates. The administration of a suspension of two selected L. reuteri isolates (6-8 x 108 colony forming units per day) to calves was performed from day 2 to day 5 after birth in a double-blinded placebo-controlled study. Clinical monitoring of the calves continued until the 14th day of life. Results Out of 46 L. reuteri isolates, only 2 met the set criteria and were used in the feeding trial. In the placebo group, 44 of 83 calves developed diarrhea within the first 2 weeks of life, whereas in the L. reuteri group this was only the case in 31 of 83 animals (p < 0.05). Conclusion L. reuteri appears to be of particular importance for the intestinal health of newborn calves. The diarrhea protective effect could be even more pronounced if an improved administration regimen is developed in terms of start, frequency, and duration.